Immediate results from biofeedback and anorectal electrostimulation in the treatment of paradoxical puborectal muscle contraction in women with obstructed defecation - Magalhães,Germana Mesquita (2018)
ABSTRACT Objective: This study was conducted to evaluate the effects of “biofeedback” (BF), electrostimulation (ES), and of the high-fiber diet associated with behavioral therapy in women with obstructed evacuation and paradoxical puborectalis contraction and to compare the results among these three modalities. Method: Thirty-one women were evaluated who fulfilled the Rome III Criteria, and with an electromanometric test positive for the presence of contraction in the evacuation maneuver. These patients were randomized into three groups: group I – conventional treatment of constipation, group II – conventional treatment of constipation associated with biofeedback and group III – conventional treatment of constipation associated with electrostimulation. At the beginning of this study and after six weeks, subjective and objective parameters of the anorectal function were evaluated using the Wexner constipation scoring system, the Bristol scale, an visual analogical scale, and anorectal electromanometry. Results: All patients demonstrated improvement in bowel satisfaction, stool frequency, effort and feeling of incomplete evacuation, stool-type modifications, and improvement in the quality of life. On examination, there was increased mean pressure of voluntary contraction in group III (p = 0.043), decreased sensitivity threshold in group II (p = 0.025) and III (p = 0.012) and decreased maximum rectal capacity in group II (p = 0.005). Only 19.4% (n = 6) had their dynamic defecation normalized, and 80.6% (n = 25) expressed clinical, non-instrumental, improvement. Conclusion: The conventional treatment of constipation, biofeedback and electrostimulation show a significant subjective improvement in symptoms of obstructed evacuation and in quality of life, regardless of the reversal of the paradoxical puborectalis contraction.